New records for the Kosovo caddisfly fauna with the description of a new species, Drusus dardanicus sp. nov. (Trichoptera: Limnephilidae) - Ibrahimi, Halil; Kučinić, Mladen; Vitecek, Simon; Waringer, Johann; Graf, Wolfram; Previšić, Ana; Bálint, Miklós; Keresztes, Lujza; Pauls, Steffen U. (Zootaxa, 2015)
The Balkan Peninsula is one of the most important European hotspots of freshwater biodiversity. The region is, however, to a large extent insufficiently investigated. Here we present data on distribution of caddisflies in one particularly understudied area, the Republic of Kosovo. Our data include the first records of Adicella altandroconia Botosaneanu & Novak and Halesus tessellatus (Rambur) for the Kosovo caddisfly fauna, and a new locality for the recently described Ecclisopteryx keroveci Previšić, Graf, & Vitecek. Further, we describe the new caddisfly species Drusus dardanicus sp. nov. from the Kopaonik Mountains. The new species belongs to the D. discophorus Species Group and differs morphologically from its most similar congeners (D. discophorus Radovanović, D. balcanicus Kumanski, and D. bureschi Kumanski) mainly in exhibiting (1) subtrianglar superior appendages; (2) a narrow, dorsal spinate area of tergite VIII; and (3) evenly rounded tips of intermediate appendages in caudal view. In phylogenetic analysis, D. dardanicus sp. nov. is well delineated and recovered as a sister taxon to D. osogovicus Kumanski, a species recorded from Bulgaria. The recent discovery of a new species and other rare or microendemic species presents important contributions to the knowledge on the rich freshwater biodiversity in Kosovo. These species face increasing anthropogenic pressure and threats to their conservation.